Perceptions of undergraduate medical students of old traditional and new CBME curriculum about pharmacovigilance and adverse drug reactions reporting at a tertiary care teaching hospital: a comparative study - Venepally, Sailaxmi; K., Indira; Jadala, Sankirth; C., Murali Krishna (International Journal of Basic & Clinical Pharmacology, 2023)
Background: National pharmacovigilance program is an ongoing program to monitor the adverse drug reactions and reporting at the earliest. The effectiveness and success of any pharmacovigilance system depends highly on the participation of all health care professionals. As medical students are future health-care givers, this study is aimed to measure perceptions on Pharmacovigilance and ADR reporting among medical students of two different curriculum. Methods: A validated and standardized KAP Questionnaire based cross sectional study. It consists of 22 questions divided into four sections of total of 22 items (six related to Personal details, eight related to knowledge, four related to attitude, and four related to practice) The filled questionnaires were collected and analyzed by MS excel Results: A comparative sample of 100 from old (phase 4) and 100 from New CBME (phase 3) curriculum undergraduate medical students of Government Medical College are included in our study. The average score of phase 3 and phase 4 medical students for knowledge was 85.37% and 75.87%, for attitude was 95.5% and 84% and for practices was 88.75% and 67.5% respectively. Conclusions: The overall knowledge, attitude and practices of new curriculum students found to be better than old curriculum students as CBME curriculum was introduced from the academic year 2019–2020 in all Medical Institutions of India to impart knowledge, communication and leadership skills using various teaching–learning methods among students.